The Effect of Picture Strip Story with Guided Questions on Students Writing Achievement - Husnawati, Wa Ode; Aderlaepe, Aderlaepe; Fatmawati, Wa Ode (Universitas Halu Oleo, 2021)
The objective of this research was to find out the effect of using picture strip story with guided questions on students’ writing achievement at SMAN 4 Baubau. This research applied quasi experimental design that consist of experimental class and control class. The sample of this research were students at class X IPS 1 and X IPS 2 in SMAN 4 Baubau who were register in academic years 2019/2020. The sample taken by using cluster random sampling and the total numbers of students are 44, 22 for experimental class (X IPS 1) and 22 for control class (X IPS 2). The research instrument was written test which focus on recount text. The researcher collected the data by giving pre-test in both of the classes, giving treatment in experimental by giving picture strip story with guided questions and non-picture strip story in control class, and giving post-test in both of the classes. In analyzing the data were used SPSS 16.0 version. To examine the hypothesis the researcher used an independent sample t-test. Based on the result, it showed that students’ mean score of post-test in experimental class is 64.50. It is raised16.73 point from its pre-test (47.77). While students’ mean score of post-test in control class is 54.91. It is only raised 11.32 point from its pre-test (43.59). Besides, the value of degree of freedom (df)= 86, t=4.034, and sig (2 tailed)=0.000. It means that the probability (sig) value is lower than α ( p value < α or 0.000 < 0.05). Therefore,picture strip story with guided questions had a significant effect on students’ writing achievement at SMAN 4 Baubau